The Impact of Low-Carbon City Construction on Urban Shrinkage: Evidence from China - Bowen Li; Meiying Huang; Quan Li (Land)
This paper uses Low-Carbon Pilot City (LCCP) as a quasi-natural experiment, 282 prefecture-level cities in China from 2007 to 2021, and models such as DID, SDM-DID, and DML to examine the impact of LCCP on urban shrinkage. Research shows that, first, LCCPs have effectively inhibited urban shrinkage, with pilot cities reducing urban shrinkage by 1.8% compared with non-pilot cities. Second, the LCCP may inhibit the city’s ability to shrink by reducing resource allocation efficiency, promoting technological innovation, and optimizing the living environment. Third, the urban shrinkage effect of the LCCP is heterogeneous depending on the economic region and whether the city is resource-based.